2013
DOI: 10.1111/ans.12196
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surgical waiting time on paediatric spinal deformity patients

Abstract: Background: Scoliosis has been shown to affect quality of life of young people. There can be a lengthy wait for surgery. We aim to assess whether the length of time waiting for surgery has an impact on quality of life and surgical outcomes. Methods: Patients who were waiting for or had completed surgery for paediatric spinal deformity in the last 3 years were contacted and asked to complete the Scoliosis Research Society-30 (SRS-30) questionnaire as well as a questionnaire designed to specifically assess the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 10 publications
0
12
0
9
Order By: Relevance
“…Due to underfunding, the surgical treatment of complex spinal deformities in publicly funded healthcare systems has been subjected to steadily lengthening waiting lists 4 - 7 . The long waiting times for deformity correction have been associated with clinical and radiological worsening of the deformity, reduced corrective potential, the need for more complex procedures, increased morbidity and complication rates, increased anxiety of patients and parents and lower scores on health-related quality of life questionnaires 8 - 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to underfunding, the surgical treatment of complex spinal deformities in publicly funded healthcare systems has been subjected to steadily lengthening waiting lists 4 - 7 . The long waiting times for deformity correction have been associated with clinical and radiological worsening of the deformity, reduced corrective potential, the need for more complex procedures, increased morbidity and complication rates, increased anxiety of patients and parents and lower scores on health-related quality of life questionnaires 8 - 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The study observed that with an increase in the length of time waiting for the surgery there was a statistically significant decrease in the domains of pain, satisfaction with the treatment, and appearance. 20 Ahn et al analyzed 88 patients with adolescent idiopathic scoliosis who were on a surgery waiting list for at least six months, and they noted a need for additional surgery in thirteen (14.8%) of the patients due to progression of the curvature as opposed to only in two (1.6%) adolescents who had been waiting for less than six months. Other findings were an increase in surgical time and in the duration of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…[2-4] Over the past decade, SRS-30 had been widely applied in different areas of quality of life of patients with different spinal deformities e.g. surgical waiting time[5], ethnic and cultural difference[6,7], satisfaction level on patients with Parkinson disease after surgery[8]. …”
Section: Introductionmentioning
confidence: 99%